Quantum‐Chemical Evaluation of Impact of Chlorination versus Fluorination on the Electronic Properties of Donors and Acceptors for Organic Solar Cells. Issue 12 (18th September 2019) - Wang, Tonghui; Brédas, Jean‐Luc
Abstract: Much attention is given to replacing fluorine with chlorine when optimizing the chemical structures of π‐conjugated polymer donors and/or non‐fullerene small‐molecule acceptors (SMAs) in order to reduce the synthetic costs for large‐scale applications of organic solar cells. To rationalize the impact of chlorination versus fluorination on the electronic properties of π‐conjugated materials, quantum‐mechanical calculations have generally been carried out at the global‐hybrid becke three‐parameter Lee‐Yang‐Parr (B3LYP) level of theory. However, B3LYP suffers from drawbacks that are especially problematic in the case of π‐conjugated systems possessing a charge‐transfer character. Here, the dipole moments and energy levels of F‐ and Cl‐containing SMA fragments, that is, 1, 2‐difluorobenzene and 1, 2‐dichlorobenzene, are reevaluated at much more robust levels of theory. The results obtained with the (optimally tuned) long‐range corrected ωB97XD functional (coming from Head‐Gordon and coworkers and including dispersion corrections) turn out very close to those calculated with the "gold‐standard" CCSD(T) (coupled‐custer with single, double, and perturbative triple excitations) method. These results, however, both markedly differ from the B3LYP findings. This confirms that, for π‐conjugated systems, tuned long‐range corrected functionals provide a reasonable compromise between accuracy and computational cost, and that much caution must be exerted when using the popular B3LYP functional. Abstract : The electronic properties of F‐ and Cl‐containing fragments of non‐fullerene small‐molecule acceptors are evaluated at different levels of theory. The comparable results obtained between the (optimally tuned) long‐range corrected functional and the CCSD(T) gold standard are markedly different from the B3LYP findings, confirming that tuned long‐range corrected functionals provide a reasonable compromise between accuracy and computational cost for π‐conjugated systems.